Unintentional experience: an important aspect of engineering `hands-on' laboratories? - Zol Bahri, Razali, Dr.; Trevelyan, James P. (American Society for Engineering Education, 2013)
Annual Conference of the American Society of Engineering Education (ASEE2008), 22nd - 25th June 2008 at Pennyslavania, USA